IMPLEMENTASI TEORI KOMUNIKASI DALAM DAKWAH - Fikri, Ibnu (At-Taqaddum, 2011)
If dakwah means ?preaching? then the dakwah has entered the area of Communication Studies. In Communication Sciences, a communicator is required to understand: 1) what message will be delivered, 2) how the message was delivered & 3) who will receive the message. There are many theories in science communication in order to a message can be achieved effectively. These theories are very important to use by scholars and practitioners of dakwah. For its implementation, dakwah requires the knowledge and theories in order the effectiveness and the success reached a maximum in the da?wah. In providing the material of religious to the object da?wah must be adapted to the conditions, circumstances and realities of mad?u upper middle class simply overwhelmed by the recitation (monologue) with no dialogue. Or conversely people with a pathetic condition be consulted regardless of the needs of the mad?u.